Maternal Low Self-Control, Maternal Attachment Toward Children, Parenting Practices, and Adolescent Low Self-Control: a Prospective 15-Year Study - Bolger, Michelle A. (Journal of developmental and life-course criminology, 2022)
Research surrounding the intergenerational transmission of self-control has expanded recently. Yet, findings are mixed, and key limitations regarding the inclusion of distinct measures of parental attachment toward children and parenting practices within a longitudinal framework remain. We seek to address these limitations by providing a longitudinal test of serial mediation linking maternal low self-control, maternal attachment toward children, maternal parenting practices, and adolescent low self-control. We employed structural equation modeling to examine direct and indirect effects between maternal low self-control measured when children were 6 months old, maternal attachment toward children measured when target children were 7 years old, maternal parenting practices assessed when children were 12 years old, and adolescent low self-control when children were 15 years old. Findings partially support assertions from self-control theory in that maternal low self-control was positively related to later adolescent low self-control indirectly via maternal attachment toward children and, in turn, maternal parenting practices. However, direct associations between maternal low self-control and maternal parenting practices and, even more, between maternal low self-control and adolescent low self-control were also observed. Limitations and implications of our findings are discussed.